HUMAN-CENTERED CONCEPTUAL METAPHORS IN PRABOWO SUBIANTO’S INTERNATIONAL DIPLOMATIC SPEECHES: A CRITICAL METAPHOR ANALYSIS IN POLITICAL DISCOURSE - Farah Fadhilah; Elvi Citraresmana; Ani Rachmat (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines how recurring human-centered metaphors construct Indonesia’s diplomatic identity and represent the country as a political actor in the international speeches of President Prabowo Subianto. Drawing on Critical Metaphor Analysis (CMA) and the Metaphor Identification Procedure (MIP), the study analyzes sixteen English-language speeches delivered during the first year of Prabowo’s presidency. Metaphorical expressions were identified through systematic linguistic analysis and subsequently interpreted through conceptual mapping and critical explanation. The findings reveal two dominant metaphorical patterns: interpersonal relationship metaphors and human body metaphors. Indonesia and its international partners are frequently represented as “friends,” “brothers,” and members of a “human family,” while global issues and national characteristics are framed through expressions such as “lungs of the earth,” “embedded in our DNA,” and “welcome with open arms.” These metaphors portray Indonesia as cooperative, inclusive, globally engaged, and environmentally responsible. At the ideological level, they function to promote solidarity, legitimacy, and mutual cooperation while simultaneously obscuring strategic interests, power asymmetries, and geopolitical tensions. The study demonstrates that human-centered metaphors serve not only as cognitive and rhetorical devices but also as ideological resources for constructing national identity and shaping international perceptions. By highlighting the role of metaphor in diplomatic communication, this research contributes to the fields of metaphor studies, political discourse analysis, and international political communication.